Frequency and Severity of Comorbid Mood and Anxiety Disorders in Prescription Opioid Dependence. (25th April 2013) - Gros, Daniel F.; Milanak, Melissa E.; Brady, Kathleen T.; Back, Sudie E.
<x xml:space="preserve">Abstract</x> Background and Objectives Comorbid substance use disorders and mood and anxiety disorders are associated with more severe psychiatric symptoms, social and occupational impairment, and economic burden. To date, the majority of research has focused on comorbidity in illicit drug users, rather than prescription drug users. To address this gap in the literature, the present cross‐sectional study investigated the clinical profiles of individuals with prescription opioid dependence with or without comorbid mood and anxiety disorders. Methods Ninety individuals with prescription opioid use were recruited to participate in the study procedures. All participants completed a structured clinical interview and series of self‐report measures. Results and Conclusions Of the 85 individuals with prescription opioid dependence, 47.1% (n = 40) were diagnosed with a comorbid mood or anxiety disorder. The findings showed that individuals with prescription opioid dependence and comorbid mood and anxiety disorders demonstrated significantly more severe alcohol use, psychiatric symptoms, and sleep impairment than individuals without comorbidity. Scientific Significance The findings highlight the frequency and severity of co‐occurring mood and anxiety disorders in individuals with prescription opioid dependence and suggest that integrated interventions are needed to address these growing problems. (Am J Addict 2013; 22:261–265)